International hydrographic survey standards - Mills, Gerald B. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1998 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Mills, G. B. (1998). International hydrographic survey standards. The International Hydrographic Review, 75(2), 97–105. https://journals.lib.unb.ca/index.php/ihr/article/view/22954